Application of Nanofibers from Electrospinning in Development of Smart Textiles for Military Clothing - Anisa Setianingsih; Khairunnisa Ulfitri; Mas Ayu Elita Hafizah (International Journal of Recent Technology and Applied Science (IJORTAS), 2025)
This paper examines the application of nanofibers produced via electrospinning in the development of smart textiles for military clothing. Smart textiles represent a significant advancement, integrating functionality with comfort to enhance traditional military garments. This study explores the potential of smart textile technology to improve the efficiency and effectiveness of military operations through capabilities such as monitoring soldiers' physiological conditions, facilitating enhanced communication, and providing protection against environmental threats. A literature review methodology was employed to analyze existing research on smart textiles in the context of military applications. This review covers technological components, benefits, challenges, and the potential of nanofibers in military clothing. The results highlight the capacity of electrospun nanofibers to improve the protective, communicative, and adaptive properties of military wear, with a focus on materials like carbon nanotubes and graphene and their applications in enhancing tensile strength, conductivity, and UV protection. This paper contributes to a deeper understanding of smart textile technology and its potential to advance the defense industry and improve the quality of protective equipment for soldiers.